2010
DOI: 10.1007/s00030-010-0088-8
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional chemotaxis kinetic model

Abstract: Abstract. In this paper, we study a variation of the equations of a chemotaxis kinetic model and investigate it in one dimension. In fact, we use fractional diffusion for the chemoattractant in the Othmar-Dunbar-Alt system (Othmer in J Math Biol 26(3): 1988). This version was exhibited in Calvez in Amer Math Soc, pp [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] 2007 for the macroscopic well-known Keller-Segel model in all space dimensions. These two macroscopic and kinetic models a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…It has been shown that the solutions to the 2D spherical symmetric kinetic model (2.9) blow up in finite time. While for the one dimensional kinetic local model (2.7), although the strict analysis is lacking [31], the numerical results strongly suggest that the solutions also blow up. In these cases, the convergence of the schemes described above would be questionable when simulations are performed on the fixed grids.…”
Section: Adaptive Grids For Solutions With Blowupmentioning
confidence: 92%
See 2 more Smart Citations
“…It has been shown that the solutions to the 2D spherical symmetric kinetic model (2.9) blow up in finite time. While for the one dimensional kinetic local model (2.7), although the strict analysis is lacking [31], the numerical results strongly suggest that the solutions also blow up. In these cases, the convergence of the schemes described above would be questionable when simulations are performed on the fixed grids.…”
Section: Adaptive Grids For Solutions With Blowupmentioning
confidence: 92%
“…We numerically check the open problem of the blow up property of the solution to the one dimensional kinetic local model (2.7). As mentioned before, a theoretical prediction on this blow up is still lacking, see [31]. We consider the initial data given by (5.1).…”
Section: The 1d Local Model: Blow Up In Finite Timementioning
confidence: 99%
See 1 more Smart Citation
“…The long time behavior of the subcritical case is unclear yet. Also, theoretic proof of the blow up in the 1D case is not available [46]. The microscopic kinetic model, with interesting properties and mysterious behaviors, make it appealing to investigate the system numerically.…”
Section: Introductionmentioning
confidence: 99%
“…The long time behavior of the subcritical case is unclear yet. Also, theoretic proof of the blow up in the 1D case is not available [46].…”
mentioning
confidence: 99%